Cognitive deficits in chronic pain patients, in a brief screening test, are independent of comorbidities and medication use - Ferreira, Karen dos Santos; Oliver, Gabriela Zucatto; Thomaz, Débora Carinhato; Teixeira, Caroliny Trevisan; Foss, Maria Paula (Arquivos de Neuro-Psiquiatria, 2016)
Objective To describe and analyze cognitive aspects in patients with chronic pain and a control group without pain.Method A case-control study was conducted on 45 patients with chronic pain and on 45 control subjects. Data including pain diagnosis, comorbidities and medication used, were evaluated. Cognitive tests, such as the Montreal Cognitive Assessment (MoCA), Verbal Fluency Test, Clock Drawing Test and Stroop Test, were applied.Results Patients with chronic pain showed a poorer performance, as shown by the scores of the MoCA test (p < 0.002), Verbal Fluency Test (p < 0.001), Clock Drawing Test (p = 0.022) and Stroop Test (p < 0.000). Chronic pain variable (p = 0.015, linear regression model) was an independent factor for results obtained with the MoCA.Conclusion Patients with chronic pain showed a poorer performance in a brief screening test for cognitive impairment not related to confounding variables, as comorbidities and pain-medication use.
Keywords: chronic pain; cognition; memory